Legacy of Amazonian Dark Earth soils on forest structure and species composition. Issue 9 (14th June 2020) - de Oliveira, Edmar Almeida; Marimon‐Junior, Ben Hur; Marimon, Beatriz Schwantes; Iriarte, José; Morandi, Paulo S.; Maezumi, S. Yoshi; Nogueira, Denis S.; Aragão, Luiz E. O .C.; da Silva, Izaias Brasil; Feldpausch, Ted R.
Abstract: Aim: Amazonian forests predominantly grow on highly weathered and nutrient poor soils. Anthropogenically enriched Amazonian Dark Earths (ADE), traditionally known as Terra Preta de Índio, were formed by pre‐Columbian populations. ADE soils are characterized by increased fertility and have continued to be exploited following European colonization. Here, we evaluated the legacy of land‐use and soil enrichment on the composition and structure in ADE and non‐ADE (NDE) forests. Location: Eastern and southern Amazonia. Time period: Pre‐Columbia – 2014. Methods: We sampled nine pairs of ADE and adjacent NDE forest plots in eastern and southern Amazonia. In each plot, we collected soil samples at 0–10 and 10–20 cm depth and measured stem diameter, height, and identified all individual woody plants (palms, trees and lianas) with diameter ≥ 10 cm. We compared soil physicochemical properties, vegetation diversity, floristic composition, aboveground biomass, and percentage of useful species. Results: In the nine paired plots, soil fertility was significantly higher in ADE soil. We sampled 4, 191 individual woody plants representing 404 species and 65 families. The floristic composition of ADE and NDE forests differed significantly at both local and regional levels. In southern Amazonia, ADE forests had, on average, higher aboveground biomass than other forests of the region, while in eastern Amazonia, biomass was similar to that of NDE forests. Species richness of both forest types did not differ and was within the range of existing regional studies. The differences in composition between large and small diameter tree recruits may indicate long‐term recovery and residual effects from historical land‐use. Additionally, the proportion of edible species tended to be higher in the ADE forests of eastern and southern Amazonia. Main conclusions: The marked differences in soil fertility, floristic composition and aboveground biomass between ADE and NDE forests are consistent with a small‐scale long‐term land‐use legacy and a regional increase in tree diversity.